Update on relapses in unilateral nephroblastoma registered in 3 consecutive SIOP/GPOH studies: a report from the GPOH-nephroblastoma study group = Unilaterale Nephroblastome: Neues zu den Rezidiven innerhalb der 3 konsekutiven SIOP/GPOH-Studien : ein Bericht der GPOH-Nephroblastom-Studiengruppe - Furtwängler, Rhoikos; Nourkami, N.; Alkassar, M.; Schweinitz, D. von; Schenk, Jens-Peter; Rübe, C.; Siemer, S.; Leuschner, I.; Graf, N. (Klinische Pädiatrie, 2011)
Introduction: Treatment and stratification of progressive/relapsed unilateral nephroblastoma (PD) has significantly evolved over the last 20 years. Early PD (≤6 months), initial high risk histology, local stage III, multiple site PD and stage IV have been implemented as high risk classification factors and novel drugs have been introduced. Patients and methods: We analysed all 251 patients having had a unilateral nephroblastoma (Stage I-IV) and progressive disease who had been treated according to SIOP9/GPO (n = 77), SIOP93-1/GPOH (n = 93) and SIOP2001/GPOH (n = 81) initially. Results: 3y-overall survival (OS) increased from 43% to 61% and 59% respectively (both p<0.01). 3y-OS for localized stage I-III rose from 43% to 65% and 68% respectively while only little improvement can be seen for initial stage IV patients with 43%, 53% and 44% respectively. Multivariate analysis confirmed high risk histology, local stage III, shorter time to PD, combined relapse as independent risk factors. 26 patients had received high-dose chemotherapy showing 64% 3y-OS compared to 54% for all non-transplanted (p=0.11). Conclusion: Structuring the treatment of progressive nephroblastoma as well as introducing new drugs have improved the outcome significantly. However improvement is depending on the specific risk profile. Very high risk tumours are often resistant to conventional treatment, hence an international uniform treatment concept is needed to achieve conclusive results in this small group. Thieme E-Books & E-Journals
Gesehen am 03.07.2023